Efektivitas Program Bantuan Langsung Tunai (BLT) Kepada Warga Penerima Manfaat di Kelurahan Menteng, Kecamatan Jekan Raya, Kota Palangka Raya - Arif; Novianti, Elsa; Pratama, Meycel; Selmai; Yonatan Ari Santoso (Jihbiz: Global Journal of Islamic Banking and Finance, 2026)
This study aims to analyze the effectiveness of the Direct Cash Assistance (BLT) program for beneficiaries in Menteng Village, Jekan Raya District, Palangka Raya City. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation. The analysis focuses on targeting accuracy, data verification and validation, and the timeliness of aid distribution.The results show that the BLT program has been relatively effective in reducing the economic burden of low-income communities. The use of a decile-based data system and the involvement of neighborhood units (RT) in verification contribute to improved targeting. However, challenges such as data inconsistencies, duplicate beneficiaries, and limited evaluation remain. From a sharia perspective, the program aligns with the principles of justice (‘adl) and public welfare (maslahah). Nevertheless, strengthening transparency, accountability, and data validation is necessary to ensure fair and sustainable distribution in accordance with Islamic economic principles.